The influence of economic and non-economic factors on the developers' decision to engage into quality subdivision and land development projects - Camarines, Leonides G.; Canaya, Faith A.; Dalisay, Michelle C.; Escartin, Ma. Adevic C.; Yanson, Anna Elisa B. (2001)
Homeownership constitutes the most significant step in life and undoubtedly it represents the most important investment. Thus, the study on the influence of economic and non-economic factors on the developers' decision to engage into quality subdivision and land development was conducted. The study aims to determine the influence of economic and non-economic factors on the decision of developers to the satisfaction of both developers and homeowners. They are many factors, which influence the developers' decision, but the researchers identified only five factors, which they think are the most important. These are income and cost for economic factors and customers' tastes and preferences, environmental considerations, and government regulations for the non-economic factors. Results of the survey is shown on the table that follows : VARIABLES-Independent-Income: Return on Investment ; Cost: Cost Feasibility ; Customer Tastes & Preferences: Survey Results ; Environmental Considerations: Survey on Occurence of Natural Phenomena ; Government Regulations: Degree of Tasks ; Dependent: Decision, Decision, Decision, Decision, Decision. PROBABILITY: 2.00% ; 0.20% ; 13.40% ; 3.60%; 59.90%. RELATIONSHIP : Significant; Significant; Non-significant; Significant ; Not significant. Based on the results of the study, it is therefore concluded that the economic factors identified by the researchers significantly affect the developers' decision to engage into quality subdivision and land development. On the other hand, of the three non-economic factors identified, only environmental considerations significantly influence the developers decision to engage into quality subdivision and land development.
Research Paper (BA 200 - Business Research). --Iloilo City : UPV-CM, March 30, 2001.